Find the integral zeroes of the polynomial p(x)=x^3-2x^2+x+4
Answers
Answered by
2
hey bro!
here ur solution:
put the factor of 4 is -1 in eq
then
==>
![= > ( - 1 {)}^{3} - 2( - 1 {)}^{2} - 1 + 4 = 0 \\ \\ = > - 1 - 2 - 1 + 4 = 0 \\ \\ = > - 4 + 4 = 0 \\ \\ = > 0 = 0 \\ \\ its \: clear \: that \: x + 1 \: is \: a \: factor \\ \: of \: the \: eq \\ \\ now = > ( - 1 {)}^{3} - 2( - 1 {)}^{2} - 1 + 4 = 0 \\ \\ = > - 1 - 2 - 1 + 4 = 0 \\ \\ = > - 4 + 4 = 0 \\ \\ = > 0 = 0 \\ \\ its \: clear \: that \: x + 1 \: is \: a \: factor \\ \: of \: the \: eq \\ \\ now](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%28+-+1+%7B%29%7D%5E%7B3%7D+-+2%28+-+1+%7B%29%7D%5E%7B2%7D+-+1+%2B+4+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+-+1+-+2+-+1+%2B+4+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+-+4+%2B+4+%3D+0+%5C%5C+%5C%5C+%3D+%26gt%3B+0+%3D+0+%5C%5C+%5C%5C+its+%5C%3A+clear+%5C%3A+that+%5C%3A+x+%2B+1+%5C%3A+is+%5C%3A+a+%5C%3A+factor+%5C%5C+%5C%3A+of+%5C%3A+the+%5C%3A+eq+%5C%5C+%5C%5C+now)
x^2(X+1) -3x(X+1)+4(x+1)
(X+1)( x^2-3x +4)
here ur solution:
put the factor of 4 is -1 in eq
then
==>
x^2(X+1) -3x(X+1)+4(x+1)
(X+1)( x^2-3x +4)
Similar questions